Volatility dynamics in Dubai gold futures market - Nekhili, R.; Thorpe, Michael (Kaizen Publishing, 2011)
This study explores the volatility dynamics of gold futures traded on the Dubai Gold and Commodities Exchange. We test the effect of margin trading reform implemented by the Emirates Securities and Commodities Authority on the dynamic relationship between the daily gold futures volatility and volume, open interest, and futures returns. We find that volatility dynamics with respect to volume and return are consistent with other futures markets patterns but not with the open interest, especially after the reform. Moreover, the reform has decreased trading volume and open interest and increased gold futures volatility.